2011
DOI: 10.1016/j.aap.2010.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pay-As-You-Drive vehicle insurance on young drivers’ speed choice: Results of a Dutch field experiment

Abstract: a b s t r a c tSpeeding is an important cause for young drivers' involvement in traffic accidents. A reduction in driving speeds of this group could result in fewer accidents. One way of reducing driving speed is offering explicit financial incentives. In collaboration with five Dutch car insurance companies, we tested the effects of a Pay-As-You-Drive insurance fee on driving speed. A group of young drivers could save money on their monthly insurance fee by keeping the speed limit. Driving speed was monitored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(109 citation statements)
references
References 23 publications
3
102
2
2
Order By: Relevance
“…The literature reports evidence of drivers modifying their driving patterns. Bolderdijk et al (2011) observed a significant impact on the reduction in speed violations among young drivers with a PAYD policy. Thus, the direct comparability of our results to the general population of driver and extrapolation of these results to all the drivers may not be valid.…”
Section: Description Of the Databasementioning
confidence: 92%
“…The literature reports evidence of drivers modifying their driving patterns. Bolderdijk et al (2011) observed a significant impact on the reduction in speed violations among young drivers with a PAYD policy. Thus, the direct comparability of our results to the general population of driver and extrapolation of these results to all the drivers may not be valid.…”
Section: Description Of the Databasementioning
confidence: 92%
“…In this regard, it has been shown that PAYD policies bring about changes in driving patterns among those who want to obtain a better premium under this pricing system. More specifically, PAYD has a positive effect on mileage reduction (as observed by [16]) and also on speed reduction (see [12]). …”
Section: Introductionmentioning
confidence: 98%
“…Many authors (including [12,13]) have discussed the advantages of commercializing PAYD policies from the perspectives of both the insurance company and the driver. For example, [14] argue that PAYD helps the insurance industry to target risk classes more effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, people will particularly engage in sustainable energy behaviors when such behavior is extrinsically rewarding (De Groot and Steg, 2009). Indeed, it was found that positive effects of financial incentives to promote ecodriving disappeared as soon as the incentives were removed (Bolderdijk et al, 2011). In addition, external incentives can inhibit positive spillover effects when subsequent actions have no clear external reward, which is not uncommon in the energy domain (Thøgersen, 2013).…”
Section: Structural Strategiesmentioning
confidence: 99%